Soft Skills Factors Affecting to Workers Performance Effectiveness of Y Generation Group in Bangkok - Proyrungroj, Pakorn; Chansom, Nakamol (Rajapark Journal, 2021)
The objectives of this research were 1) to examine the differences in demographic factors which can affect the efficiency of Generation-Y workers’ performance in Bangkok and 2) to investigate the soft skills which can affect the efficiency of Generation-Y workers’ performance in Bangkok. Regarding the research methodology, both quantitative and qualitative research was applied. According to the quantitative research, the primary objective was to investigate the causality by a survey. Therefore, the phenomenological method was selected by using an in-depth interview; moreover, the two key-informant groups were represented in the research. Firstly, 400 respondents were the group of workers in private companies born in 1980-1995 or the ages of 26 to 41 in Bangkok. Secondly, the group of Generation Y managers living in Bangkok had at least one year of experience at the manager level. Five interviewees had in-depth interviews. For the data collection, the research instruments consisted of the questionnaire and the semi-structured interview form. For the data analysis, statistical methods were applied: percentage, mean, standard deviation, multiple correlation analysis, and multiple regression analysis. The results revealed that gender, educational level different and soft skills included adaptability, teamwork, creativity, and persuasion skills; they could affect the efficiency of performances by developing soft skills in an organization to support some abilities and potential during the performances and the improvement. In addition, the company perspectives on soft skills could be improved to grow and enhance operational efficiency in organizations.